The Basque seroras : local religion, gender, and power in northern Iberia, 1550-1800 - Scott, Amanda L. (Cornell University Press, 2020)
"This book looks at a largely overlooked category of devout laywomen called seroras and examines the ways women and their communities crafted surprisingly powerful religious positions for women outside of the confines of monasticism or marriage, right at the time when which we usually think of the Reformations as effectively limiting and tightly controlling female religious experimentation"--